Does Heart Valve Team Risk Assessment Predict Outcomes after Transcatheter Aortic Valve Replacement? - Catalano, Michael A.; Rutkin, Bruce; Kohn, Nina; Hartman, Alan; Yu, Pey-Jen (International Journal of Angiology, 2020)
Consideration for transcatheter aortic valve replacement (TAVR) necessitates an integrated risk assessment by members of the Heart Valve Team. The utility of the integrated risk assessment for predicting TAVR outcomes is not established. This article aims to compare the utility of the integrated risk assessment to that of the Society of Thoracic Surgeons Predicted Risk of Mortality (STS-PROM) score for predicting patient outcomes after TAVR. A total of 274 patients who underwent TAVR from January 2016 to August 2017 were included in this study. Patients were deemed intermediate or high risk by two surgeons on the Heart Valve Team based on an integrated risk assessment that incorporates the STS-PROM score, fragility measures, end-organ dysfunction, and surgeon evaluation. Patients were also deemed low, intermediate, or high risk based solely on their STS-PROM scores of <3%, ≥3% to <8%, and ≥8%, respectively. Differences in postoperative outcomes between intermediate- and high-risk groups as categorized by the integrated risk assessment versus STS-PROM were compared. There were no statistically significant differences in postoperative outcomes between patients who were deemed high and intermediate risk by the Heart Valve Team risk assessment. In contrast, postoperative complication rates were significantly higher in patients deemed high risk as compared with intermediate risk by STS-PROM. Integrated risk assessment by the Heart Valve Team is not superior to STS-PROM in predicting postoperative outcomes in patients undergoing TAVR.
Keywords: aortic valve disease; risk factors; heart team; transcatheter; valve replacement; risk score; outcomes